2017
DOI: 10.1016/j.acthis.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Histological and immunohistochemical characterization of the Mongolian gerbil’s mammary gland during gestation, lactation and involution

Abstract: The morphological description of normal tissues is fundamental for making comparisons and in order to identify injuries and lesions. The aim of this work was to describe the morphological characteristics of the female Mongolian gerbil's (Meriones unguiculatus) normal mammary gland, the average expression of hormone receptors, and the average proliferation rates in the epithelial cells during the periods of lactation, pregnancy and involution. Dams were euthanized on the 14th and 21st gestational days, 7 and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…In addition, our data indicate that the mammary gland in the gerbil remains highly proliferative in postlactational involution, which corroborates a previous study (Leonel et al, 2017), conversely to what is seen in other laboratory rodents in which there is a decrease in epithelial proliferation during this period (Allan, Beattie, & Flint, 2004). Our data also indicate an intense process of angiogenesis in the gland during involution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, our data indicate that the mammary gland in the gerbil remains highly proliferative in postlactational involution, which corroborates a previous study (Leonel et al, 2017), conversely to what is seen in other laboratory rodents in which there is a decrease in epithelial proliferation during this period (Allan, Beattie, & Flint, 2004). Our data also indicate an intense process of angiogenesis in the gland during involution.…”
Section: Discussionsupporting
confidence: 93%
“…Among laboratory rodents, the Mongolian gerbil is known for its easy handling and high susceptibility to pathological conditions (Sanches et al, 2014, 2020; Santos & Taboga, 2006), being used in experiments on physiology, development, and pathogenesis in several organs (Biancardi, Dos Santos, de Carvalho, Sanches, & Taboga, 2017; Christante, Taboga, Pinto‐Fochi, & Góes, 2013; Perez et al, 2012; Sanches et al, 2017; Santos et al, 2008), including the mammary gland. It was found that the adult mammary gland in gerbils presents a more proliferative profile during reproductive life compared to other laboratory rodents, such as rats and mice, in addition to a possible greater susceptibility to tumorigenesis (Leonel, Falleiros, Campos & Taboga, 2017), but the dynamics of mammary gland involution in the gerbil and the possible function of telocytes remain poorly understood. Therefore, this study aims to evaluate the presence of telocytes in the mammary gland in gerbils during postlactational involution, as well as a possible role for these cells.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the carbohydrates in the secretion of the lactating mammary gland, Ellen et al (2017) and Swapna et al (2020) used PAS stain during different stages of milk production. The results of these studies revealed that the intensity of the PAS reaction differed throughout the milk production process in a direct correlation to the level of carbohydrates and mucins in the secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Mammary gland tissues were examined using a Nikon eclipse inverted microscope (Nikon Corp., Tokyo, Japan), and the area (µm 2 ) of secretory epithelium and fat cells and the area of stroma were calculated using the NIS-element imaging system from the same manufacturer. The ratio of the area of the secretory epithelium and fat cells to the area of the stroma was then calculated ( 16 ). Ki-67 staining was used to demonstrate tissue stimulation and proliferation in the endometrium, mammary glands, and ovaries.…”
Section: Methodsmentioning
confidence: 99%